PENGARUH KEBAJIKAN, INTEGRITAS, KOMPETENSI, DAN KUALITAS INFORMASI TERHADAP INTENSI MEMBELI PRODUK DI INSTAGRAM - Purnama Jaya Susilo; Dwinita Laksmidewi (Universitas Multimedia Nusantara, 2022)
Abstract - The Instagram application is currently a popular application for selling products, including fashion products, by young people in Indonesia society. This study aims to examine the effect of perceived benevolence or the perception that stores on Instagram do good things, the integrity or honesty of stores, the competence, and the quality of the information provided by stores on Instagram, on purchase intentions. The research was conducted using a survey method, with consumer respondents who shop online for fashion products on Instagram. Hypothesis testing using mediation test with SPSS macros. The results show that perceived benevolence, integrity, and competence have a positive effect on purchase intention and are significantly mediated by consumer trust. Keywords: Perceived Benevolence; Integrity; Competence; Quality of Information; Trust; Instagram